Rice husk cement-based composites for acoustic barriers and thermal insulating layers. (July 2021) - Marques, Beatriz; Almeida, João; Tadeu, António; António, Julieta; Santos, Maria Inês; de Brito, Jorge; Oliveira, Micaela
Abstract: This work evaluates the performance of cement-based composites made with rice husk and intended to be used in acoustic barriers and as thermal insulating material in a multilayer system. Because acoustic barriers are exposed to external conditions and mechanical loads, a wide range of laboratory tests were performed to evaluate the mechanical, durability and acoustic characteristics of the composites. Their specific heat capacity and thermal conductivity were evaluated when used as an insulation layer. Other cement-based composites that incorporate treated wood and rubber granules were studied for comparison purposes. The environmental performance of these new cement-based composites was evaluated by means of a life cycle assessment (LCA). It was found that those that contain rice husk are suitable for coating acoustic barriers, since it offers a good mechanical, durability, and acoustic performance. It was also found that rice husk cement-based composites can be used as thermal insulation layer. The LCA further demonstrated the good performance of the rice husk composites compared with those containing treated wood and rubber granules. Highlights: Development of innovative cement-based composites with natural rice husk. Mechanical results highlight the importance of aggregates' porosity and geometry. Composites with RH are more sensitive to temperature differences than to frosting. Low apparent bulk density of rice husks contributes to improve thermal performance. The use of local by-products contribute to improve the environmental performance.